Você está na página 1de 13

π

r d = 2r π C d

π = C d

C

2r

=

π

C = π d = 2 π r

2

1 1 o 360 360 o

1 1

1

180 o

90 o

1

r

0 o 360 o

s = r

270 o

r θ s s 3

1 = θ

r

s

s = r θ

3

1 = x

r 2 π r

x = 2 π

2 π

s = r θ

θ

r

90 o =

π

2

0 o = 0 360 o = 2 π

θ

180 o = π

270 o =

3π

2

θ x 3

π = x

180

o

θ o

x =

θ

180 π

155 o

π = x

180

o

155

o

x = 155

180 π = 31

35 π

3

4 π

π

3

4 π

=

180

o

x

x =

3 π 180

4

π

= 135 o

OP Q

OP = 1

cos(θ) = OQ/OP = x/1 = x

sen(θ) = P Q/OP = OR/OP = y/1 = y,

P

P = (x, y) = cos(θ), sen(θ) .

 ✻ y (1, 0) ✲ x

R

θ

P (x, y)

O

Q

P (x, y) θ P P

 P (x, y) ❅ ❅ ❅ ❅ ✻ R θ Q O ✲
 ✻ Q θ P (x, y) O R
 ✻ θ Q O R ❅ ✲ ❅ ❅ ❅ P (x, y)

2 o

3 o

4 o

cos(θ) = OQ = x sen(θ) = OR = y

2 sen(θ) > 0 cos(θ) > 0

0 < θ <

π < θ < π sen(θ) > 0 cos(θ) < 0

π

2

π < θ < 3π

2

sen(θ) < 0 cos(θ) < 0

3π < θ < 2π sen(θ) < 0 cos(θ) > 0

2

x x sen(x) f (x) = sen(x) sen(x)

T = 2π 2π 2π x R sen(x) = sen(x + 2π)

1 1 x R 1 sen(x) 1

sen(x)

 ✻ ✲

4π

3π

2π

π

0

π

2π

3π

4π

sen(x)

x

x x cos(x) f (x) = cos(x) cos(x)

T = 2π 2π 2π x R cos(x) = cos(x + 2π)

1 1 x R 1 cos(x) 1

α α

 sen(α) = QR = − QS = −sen(−α) ∴ sen(α) = −sen(−α). cos(α) = OQ = cos(−α) ∴ cos(α) = cos(−α).

 tg(α) = sen(α) cos(α) = −sen(−α) cos(−α)

= tg(α)

tg(α) = tg(α).

cos(x)

 ✻ ✲

4π

3π

2π

π

0

π

2π

3π

4π

cos(x)

 ✻ R α O ❅ ❅ ❅ ❅ −α ❅ Q S ✲

sen(α) = sen(α)

cos(α) = cos(α)

tg(α) = tg(α)

x

α α π

2

OR = OQ

OP = OS

sen(α) = cos α π ,

2

cos(α) = sen α π .

2

OQ = OR

OS = OP

cos(α) = sen α + π .

2

sen(α) = cos α π .

2

α α + π

2

 ✻ α R S ✲ P O Q

α π

2

α α π

2

 α + π ✻ 2 R S α ✲ P O Q

α α + π

2

Q = cos(α), sen(α)
P
α − β
α
β
O

= cos(β), sen(β)

cos(α β)

P Q

 PQ 2 = cos(α) − cos(β) 2 + sen(α) − sen(β) 2 = cos 2 (α) − 2cos(α)cos(β) + cos 2 (β) + sen 2 (α) − 2sen(α)sen(β) + sen 2 (β) = cos 2 (α) + sen 2 (α) + cos 2 (β) + sen 2 (β) − 2cos(α)cos(β) − 2sen(α)sen(β) = 1 + 1 − 2cos(α)cos(β) − 2sen(α)sen(β) = 2 − 2 cos(α)cos(β) + sen(α)sen(β)

OP Q

 PQ 2 = OP 2 + OQ 2 − 2 OP OQ cos(α − β) = 1 + 1 − 2cos(α − β) = 2 − 2cos(α − β)

P Q 2

cos(α β) = cos(α)cos(β) + sen(α)sen(β)

cos(α + β) = cos α (β) = cos(α)cos(β) + sen(α)sen(β)

cos(α + β) = cos(α)cos(β) sen(α)sen(β)

sen(α β) = cos α β π = cos α β + π

2

2

sen(α β) = cos(α)cos β + π + sen(α)sen β + π .

2

2

cos β + π = cos(β)cos π sen(β)sen π = sen(β)

2

2

2

sen β + π = cos(β).

2

sen(α β) = sen(α)cos(β) cos(α)sen(β)

sen(α + β) = sen α (β) = sen(α)cos(β) cos(α)sen(β)

sen(α + β) = sen(α)cos(β) + cos(α)sen(β)

 cos(α − β) = cos(α)cos(β) + sen(α)sen(β) cos(α + β) = cos(α)cos(β) − sen(α)sen(β) sen(α − β) = sen(α)cos(β) − cos(α)sen(β) sen(α + β) = sen(α)cos(β) + cos(α)sen(β)

1 o

2 o

0 < θ < π

2

π < θ < π

2

3 o π < θ < 3π

2

4 o 3π < θ < 2π

2

θ θ 3

π < θ < π π θ

2

sen(θ) = OR = sen(π θ)

cos(θ) = OP = OQ = cos(π θ)

 ✻ θ ❅ ❅ ❅ ❅ R ❅ π − θ P O Q ✲
 ✻ P R θ − π θ ✲ O S Q
 ✻ R 2π − θ O S ❅ ❅ ❅ ❅ ❅ Q θ ✲

2 o 1 o

3 o 1 o

4 o 1 o

tg(θ) = tg(π θ)

ctg(θ) = cotg(π θ)

sec(θ) = sec(π θ)

csc(θ) = csc(π θ)

5π π 5π = π

6

6

6 π

2

<

5π

6

< π

sen 5π = sen π =

6

6

1 cos 5π = cos π = − √ 3

2

2

6

6

π < θ < 3π

2

sen(θ) = OS = OR = sen(θ π)

cos(θ) = OP = OQ = cos(θ π)

θ π

tg(θ) = tg(θ π)

ctg(θ) = cotg(θ π)

sec(θ) = sec(θ π)

csc(θ) = csc(θ π)

5π

5π π = π

4

4

4

π < 5π

4

<

3π

2

sen 5π = sen π = − √ 2

4

4

2

cos 5π = cos π = − √ 2

4

4

2

3π

2

< θ < 2π 2π θ

sen(θ) = OS = OR = sen(2π θ)

cos(θ) = OQ = cos(2π θ)

tg(θ) = tg(2π θ)

ctg(θ) = cotg(2π θ)

sec(θ) = sec(2π θ)

csc(θ) = csc(2π θ)

5π

3 3π

2

2π 5π = π

3

3

<

5π

3

< 2π

sen 5π = sen π = − √ 3

3

3

2

cos 5π = cos π = 1

2

3

3

seno cosseno tangente cotangente secante cossecante 1 o

 θ sen(θ) cos(θ) tg(θ) 0 0 1 0 π 1 √ 3 √ 3 6 2 2 3 π √ 2 √ 2 1 4 2 2 π √ 3 1 √ 3 3 2 2 π 1 ∃ 2

1 o

1 o

 ✻ π 2 2π π 3 3π 4 5π 6 3 π 4 6 π π 0 ✲ 7π 6 5π 4 4π 3 3π 5π 3 7π 4 11π 6 2

sen(x) = 0

x = 0 x = π

x = kπ, k Z.

sen(x) = cos(x)

x = π x = 5π

4

4

π

4

x = π + kπ , k Z.

4

2cos(x) 1 = 0

cos(x) = 2 x = π

3

π

3

1

x = 5π = π

3

3

x = 2± π

3

, k Z.

225 o

1 12

50

α β γ sen(α) < 0 cos(α) < 0 cos(β) < 0 tg(β) < 0 sen(γ) > 0 cotg(γ) > 0

sen(π/4) + cos(π/4) + cos(π/2 + π/4)

R R f (x) = 1 + 4sen(x)

R R f (x) = 2sen(x) 3

sen(x) = a cos(x) = 2 a 1

sen(x) = k 1 cos(x) =

3 k 2

2sen 2 (x) tg 2 (x)

cos 2 (x)

sec(x)+sen(x)

cossec(x)+cos(x)

1+cos(x) + 1+cos(x

sen(x)

sen(x)

3

5

sec(x) = 3 tg(x) < 0

y =

2tan(x)

1tan 2

(x) cos(x) = 3

7

tg(x) = 7 π < x < π sen(x)

7

2

cos(3x π ) = 0

5

tan(x) < 0

1 4cos 2 (x) = 0 0 π

3 cos(2x) = 1

1

cos(2x) = 2 [π, π]

x sen(x) = sen(x + π) 0 x 2π

cos(x) = cos( π x) 0 < x < 2π

3

tg(x + 1) 3cotg(x) 1 = 0 [0, π]

x tg(x) + cotg(x) = 2

x sen 2 (x) = 1+cos(x) [0, 2π]

2

x sec 2 (x) + 2tg 2 (x) = 2 [0, 2π]

1

cos 2 (x) sen 2 (π x) = 2 [0, π]

sen 2 (x) + sen(x) = 0 [0, 2π]

1

cos 2 (x)

1+sen(x) +

1

1

1sen(x) =

x 2 cos(x) + sec(x) = 5

3 1 cos(x) = sen 2 (x)

sen 3 (x) 3sen 2 (x)cos(x) + 3sen(x).cos 2 (x) cos 3 (x) = 0

[0, 2π]

sen(x) = 12

13

sen(y) = 4 0 < x, y < π sen(x y)

5

2

cos(x) = 3 sen(x − π )
5
2
sen(x) = √ 2 x
2

sen(x π )cos(x π ).

2

2

2tg(x)

1+tg 2

(x) sen(2x)

sen(x) = 3 cos(2x)

6

2

sen(x) = 3 x sen(2x)

cos(36 o ) = 1+ 5 cos(72 o )

4

x cos(5x)

1

2

2.cos 2 (x) > cos(x) [0, π]

0 x π

1

cossec(x)

sec(x) > 0